Omnichannel Marketing Strategy and Its Impact on Customer Satisfaction: A Study in Southeast Asia - Pane, Sri Rezeki; Azizah; Zamaludin; Apriyandi, Adek (Outline Publisher, 2025)
This study aims to analyze the influence of omnichannel marketing strategies on customer satisfaction levels in Southeast Asia. The application of the omnichannel marketing concept is becoming increasingly important as the integration of online and offline channels in modern consumer shopping activities increases. This study used a descriptive quantitative approach with a survey method involving 400 respondents from four countries: Indonesia, Malaysia, Thailand, and Singapore. Data were collected through an online questionnaire and analyzed using multiple linear regression techniques to determine the influence of each dimension of the omnichannel strategy on customer satisfaction. The results of the study indicate that omnichannel marketing strategies have a positive and significant impact on customer satisfaction. Channel integration is the most dominant factor in increasing satisfaction, followed by service personalization and ease of access to information. Customers in Southeast Asia highly value a consistent and connected shopping experience across online and offline channels. Furthermore, variations in shopping behavior across countries were found, with customers in Singapore and Malaysia prioritizing the efficiency of digital channels, while customers in Indonesia and Thailand still rely on a combination of online and offline channels. These findings offer important implications for retail and e-commerce companies in Southeast Asia to strengthen system integration, enhance customer data-driven personalization, and adapt marketing strategies to local market characteristics. Overall, this study confirms that omnichannel marketing strategies are key to building customer satisfaction and loyalty in the increasingly competitive digital era.